Analisis Kemampuan Berpikir Tingkat Tinggi Peserta Didik Materi Volume Bangun Ruang - Junandi Fahri; Vidya Setyaningrum (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2023)
This study aims to determine the profile of students' higher-order thinking skills on the material of volume of space in class VI SDN 34 Pontianak Kota. The subjects in the study amounted to 94 students taken from three classes taught by mathematics teachers, namely classes VI A, VI B, and VI D. The approach in study used a quantitative approach with descriptive research type. The research data was taken by giving a problem analysis test to students who became research subjects. The results showed that as many as 98.2% of students had low higher-order thinking skills and 2.2% had moderate higher-order thinking skills. Students’ low level of thinking ability is caused by several factors and obstacles experienced by students when working on problems. Factors that influence this include students’ lack of motivation to answer the questions given and the lack of practice in working on HOTS questions in the form of story problems. In addition, the obstacles found when students work on problems are not understanding the problem correctly which has an impact on the wrong calculation and determination of the formula used when answering the problem.